A functional requirement model of e-learning system in secondary school in Dhi-Qar province, Iraq - Hussein, Raed Mohammed (2016)
Recently, the modern technology simplifies the learning programs and support communication among students, teachers, parents, and the managements of schools in educational institutions. With this development, the existing electronic learning requirements do not meet all students’ or the educational institution’s needs, due to the varying students’ needs, goals, backgrounds, knowledge levels, and learning capabilities. Furthermore, prior literature also reveals some disadvantages of current online environment systems, including lack of interaction among users and difficulty of supporting co-operative work. On the other hand, the unstable environment and the insecure situation that Iraq currently faces prompts parents to avoid sending their children to school. In addition to that, in some parts of Dhi-Qar, there are three schools running in one building, operating at different times and there is a dearth of learning materials. With regard to requirement model, there is a lack of requirement model to develop the e-learning system specifically for the secondary school. In accordance to that, this study seeks to propose a functional requirement model of e-learning system to link the stakeholders or actors of the educational process in online environment. Data were collected through interviews and questionnaires. The user requirements were obtained from literature review and interview with users. They were translated into a prototype, which was designed using an open source platform, Moodle. Finally, acceptance and usability evaluation were conducted, using questionnaires. The results reveal that the participants are satisfied with the proposed requirements, and these requirements meet all the stakeholders’ needs. Therefore, the model proposed in this study can be used for particular education institutions and other conflict areas to complement the existing traditional classrooms.